PPAR𝛾, PTEN, and the Fight against Cancer - Rosemary E. Teresi; Kristin A. Waite (PPAR Research)
Peroxisome proliferator-activated receptor gamma (PPAR𝛾) is a ligand-activated transcription factor, which belongs to the family of nuclear hormone receptors. Recent in vitro studies have shown that PPAR𝛾 can regulate the transcription of phosphatase and tensin homolog on chromosome ten (PTEN), a known tumor suppressor. PTEN is a susceptibility gene for a number of disorders, including breast and thyroid cancer. Activation of PPAR𝛾 through agonists increases functional PTEN protein levels that subsequently induces apoptosis and inhibits cellular growth, which suggests that PPAR𝛾 may be a tumor suppressor. Indeed, several in vivo studies have demonstrated that genetic alterations of PPAR𝛾 can promote tumor progression. These results are supported by observations of the beneficial effects of PPAR𝛾 agonists in the in vivo cancer setting. These studies signify the importance of PPAR𝛾 and PTEN's interaction in cancer prevention.